Mental Health Consequences of Unemployment: Mental Health, Somatic Symptoms, Depressive Affect and Positive Affect - Setati, Tsholofelo (School of Economics, 2021)
In this dissertation, we endeavoured to investigate the relationship between mental health and labour market changes in South Africa. We started by understanding the relationship between the aggregate CESD-10 and labour market status and then explored whether this aggregate relationship holds true for each of the three mental health factors that make up the CESD-10 score. Using data from the National Income Dynamics Study, waves 1-5, we documented increasing mental health symptoms with employed to other states of unemployment. This follows for somatic symptoms, depressed affect and positive affect, but the source driving the effects differs between factors and with the CESD-10 as well. We found that those who are NEA suffer to a greater extent in positive affect than in the other two factors relative to the employed. For those who are unemployed (discouraged), we see they also experience the strongest detrimental effect to their positive affect relative to the employed. However, they experience lower depressed affect scores relative to the employed. Those who are unemployed (strict), meanwhile, experience greater depressed affect scores out of the three factors when compared to the employed. As such, we expect to see an average increase in depressive symptoms classifications among those moving from employed to NEA statuses. We can also expect an average increase in depressed affect disorder classifications among those moving from employed to NEA labour force status. Likewise, we can expect higher positive affect across the five waves among those moving from a employed to NEA status. We find that, after controlling for observed individual characteristics and utilizing the panel structure of the data by allowing for individual specific fixed effects, negative labour market shifts have a significant negative impact on mental health. The sub-group analysis shows that this has a particularly adverse effect on black people and males.